(untitled) (LEGAL DIALOGICA, 2025)
This study aims to determine and analyze the legal protection provided to Grab food couriers (Grabfood) in dealing with fictitious order cases, as well as to examine legal solutions that can be applied to provide compensation to couriers who are harmed by fictitious orders. The method used in this study is empirical method research. Based on the results of the study, it was concluded that Legal protection for Grabfood couriers who experience fictitious orders, there is no special regulation that requires companies to provide protection for Grabfood couriers who experience fictitious orders, but Grabfood couriers can use Article 1365 of the Civil Code concerning unlawful acts and Article 1243 of the Civil Code regulating Default as a legal basis if they experience such problems. The legal solution provided to partners who experience fictitious orders, namely the government is required to issue preventive regulations by creating a special law regulating protection for online motorcycle taxi couriers who experience fictitious orders. Abstrak: penelitian ini bertujuan Untuk mengetahui dan menganalisis terkait perlindungan hukum yang diberikan kepada kurir Grab makanan (Grabfood) dalam menghadapi kasus pesanan fiktif, serta mengkaji solusi hukum yang dapat diterapkan untuk memberikan ganti rugi kepada kurir yang dirugikan akibat pesanan fiktif. Metode yang digunakan dalam penelitian ini adalah penelitian metode empiris. Berdasarkan hasil penelitian maka diperoleh kesimpulan bahwa Perlindungan hukum bagi kurir Grabfood yang mengalami pesanan fiktif belum ada regulasi khusus yang mewajibkan perusahaan untuk memberikan perlindungan bagi kurir Grabfood yang mengalami pesanan fiktif, namun kurir Grabfood dapat menggunakan Pasal 1365 KUHPerdata tentang perbuatan melawan hukum dan Pasal 1243 KUHPerdata mengatur tentang Wanprestasi sebagai lamdasan hukum jika mengalami masalah tersebut. Solusi hukum yang diberikan kepada mitra yang mengalami pesanan fiktif, yaitu pemerintah wajib mengeluarkan regulasi pencegahan dengan menciptakan Undang-Undang khusus yang mengatur tentang perlindungan terhadap kurir ojek online yang mengalami pesanan fiktif.